An evaluation of recruitment methods utilized for a clinical trial with periodontal and diabetes enrollment criteria: the Diabetes and Periodontal Therapy Trial. (December 2014) - Schoenfeld, Elinor R; Hyman, Leslie; Simpson, Leslie Long; Michalowicz, Bryan; Reddy, Michael; Gelato, Marie; Hou, Wei; Engebretson, Steven P; Hytner, Catherine; Lenton, Pat; ,
Background: Diabetes and its complications are a major United States public health concern.Methods : The Diabetes and Periodontal Therapy Trial (DPTT) evaluated whether non-surgical treatment of periodontal disease influenced diabetes management among persons with Type 2 diabetes and periodontitis. The aim of this study was to evaluate DPTT's many recruitment strategies in terms of enrollment success.Results/Conclusion: Targeted recruitment strategies were more effective in identifying individuals who met periodontal and diabetes eligibility criteria. Individuals eligible for a baseline visit/enrollment were more often male, had a younger age at diabetes diagnosis, a longer diabetes duration, more often Hispanic and less often African–American. Tracking and evaluating recruitment sources during study enrollment optimized recruitment methods to enroll a diverse participant population based upon gender, race and ethnicity.